2017
DOI: 10.1002/jcla.22284
|View full text |Cite
|
Sign up to set email alerts
|

Quality specifications of routine clinical chemistry methods based on sigma metrics in performance evaluation

Abstract: Sigma metrics are an optimal tool to evaluate the performance of different assays. An assay with a high value could use a simple internal quality control rule, while an assay with a low value should be monitored strictly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
(15 reference statements)
1
17
0
1
Order By: Relevance
“…from Belgium and Xia J et al. from China [ 3 , 17 ]. Further for analytes showing poor performance in terms of σ ​< ​3, the cause for poor performance was evaluated using QGI index similar to study performed by Verma M et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…from Belgium and Xia J et al. from China [ 3 , 17 ]. Further for analytes showing poor performance in terms of σ ​< ​3, the cause for poor performance was evaluated using QGI index similar to study performed by Verma M et al.…”
Section: Discussionmentioning
confidence: 99%
“…and Xia J et al. [ 3 , 17 ] Using biological variability data, σ metrics ranged from 0.8 to 8.02 for Level-2 and from 0.84 to 9.77 for Level-3. Performance analysis for 14 parameters revealed σ ​< ​3 (poor performance) for 5 parameters of level 2 IQC (AST, Total protein, Glucose, BUN and ALT), 2 analytes of level 3 IQC (BUN, ALT) using TEa values as per CLIA guidelines while using Biological Variability data guidelines; poor performance (σ ​< ​3) was seen for 10 parameters of level 2 IQC (AST, ALP, Alb, Total protein, Glucose, BUN, creatinine, ALT, Ca and HDL), 5 analytes of level 3 IQC (ALP, Alb, Total Protein, Glucose and HDL).…”
Section: Discussionmentioning
confidence: 99%
“…These authors therefore suggested that no less than two concentrations of quality control products should be used every day for internal quality control to ensure acceptable test results . Xia et al also showed that sigma metric is a useful tool to evaluate assay performance and suggested that an assay with a high sigma value could use a simple internal quality control rule, whereas an assay with a low sigma value should be monitored strictly. The conclusions of our study are in agreement with the results of the above scholars, indicating that sigma metrics can play an important role in the field of quality control.…”
Section: Discussionmentioning
confidence: 99%
“…2 Sigma metric has become a useful tool to monitor quality indicators, 1 to assess the analytical quality of assays, 3,4 to set quality control rules, [5][6][7][8] to describe assay analytical performance for external quality assessment participants, 9 and to help manufacturers choose product requirements. 8,11 Thus, laboratories have to take into account which TEa specification is most appropriate initially. The TEa from various sources, such as the Clinical Laboratory Improvement Amendments (CLIA), the College of American Pathologists (CAP), Reference Institute for Bioanalytics (Rilibak), the Royal College of Pathologists of Australasia (RCPA), and the China National Center for Clinical Laboratories (NCCL) external quality assessment goals, is associated with significantly different Sigma metrics for the same assay.…”
Section: Sigma (σ) Metric Was First Introduced Into Clinical Laboratomentioning
confidence: 99%
“…The TEa from various sources, such as the Clinical Laboratory Improvement Amendments (CLIA), the College of American Pathologists (CAP), Reference Institute for Bioanalytics (Rilibak), the Royal College of Pathologists of Australasia (RCPA), and the China National Center for Clinical Laboratories (NCCL) external quality assessment goals, is associated with significantly different Sigma metrics for the same assay. 8,11 Thus, laboratories have to take into account which TEa specification is most appropriate initially.…”
Section: Introductionmentioning
confidence: 99%